Komposisi Kandungan Senyawa Flavor Non Volatil Selada Laut (Ulva lactuca) Segar dan Kering - Gabriela, Lisa; Rusky Intan Pratama; Junianto; Iis Rostini (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2025)
Drying has the potential to alter the physical, chemical, and organoleptic characteristics of food materials. This study aims to identify the composition of non-volatile flavor compounds in fresh and dried sea lettuce (Ulva lactuca). The identification of non-volatile flavor compounds was conducted using amino acid profiling through High-Performance Liquid Chromatography (HPLC). The organoleptic characteristics, including appearance, aroma, texture, and taste of fresh and dried sea lettuce samples, were assessed through a simple descriptive test. The quantitative amino acid analysis data and the descriptive test results were analyzed using a comparative descriptive method. The findings revealed that both fresh and dried Ulva lactuca contain 17 types of amino acids, comprising 9 essential amino acids and 8 non-essential amino acids, which influence flavor characteristics. The descriptive test indicated that fresh Ulva lactuca is characterized by clean, shiny, and soft light green to dark green sheets with an elastic texture and a distinctive fresh seaweed aroma. In contrast, dried Ulva lactuca exhibited a yellowish-green color, a stiff and brittle texture, and a stronger salty taste with a slight umami sensation. These findings highlight the potential of Ulva lactuca as a versatile ingredient in food product development, particularly for enhancing flavor and nutritional value.